A randomised, controlled trial of meditation and yoga in permanent atrial fibrillation: the MAYA study. (14th October 2021) - Kodliwadmath, A; Duggal, B; Ray, I B; Singh, A; Nanda, N; Hiremath, B
Abstract: Background: The role of yoga in paroxysmal atrial fibrillation (AF) is known. But its role in permanent AF has not been studied. Purpose: The objectives of our study are to evaluate the effects of yoga on symptoms, heart rate, quality of life, hospitalisations, medication adherence and echocardiographic parameters in permanent AF. Methods: We conducted a single centre, randomised, participant blinded, parallel group, sham-controlled study between October 2019 and September 2020. We included patients aged 18–65 years with permanent AF due to any cause. Patients in New York Heart Association (NYHA) class≥3, modified European Heart Rhythm Association (mEHRA) class ≥3 and left ventricular ejection fraction (LVEF)<30% were excluded. Total of 84 patients underwent randomisation into two groups of 42 each. None of the participants had prior knowledge or contraindications to yoga. Subjects in yoga arm underwent supervised and self-performed yoga sessions consisting of various asanas, pranayamas and dhyana, while those in the sham arm underwent supervised and self-performed joint exercises, each session lasting for 60 minutes/day for 6 days a week along with guideline directed medical therapy in both arms. The primary endpoints were improvement in NYHA class, mEHRA class, heart rate at rest and after 6 minute walk test, 6 minute walk distance, quality of life, medication adherence, hospitalisations, LVEF and left atrial volume index at 3 months. The secondary endpoints included the same parameters assessed at 1month. Quality of life was assessed by the short form (SF)-36 questionnaire which has eight domains. Scores for each domain range from 0 to 100, with a higher score defining a more favourable health state. All analyses were based on intention to treat principle. Results: The groups were well-matched at baseline. The mean age of study participants was 50.62±12.97 years, 56% were women and the most common risk factor was rheumatic heart disease found in 47.6% of the cases. Four patients in the yoga group and 3 in the sham group were lost to follow up. There was significant improvement in various parameters in the yoga arm at 1 and 3 months. (Figures 1 and 2). Hospitalisation at 3 months was lower in the yoga arm (0.73±0.81) versus sham arm (1.13±0.93); p=0.044. Out of 38 patients in the yoga arm, 6 patients had improvement in the medication adherence compared to 9 patients (out of 39) in the sham arm at 3 months, p=0.419, OR (95% CI) = 0.62 (0.19–1.96). Higher the compliance to yoga, defined by the number of sessions per week, more was the improvement in various parameters. No harms were noted. Conclusion: Among patients of permanent AF already on medical therapy, yoga significantly improves symptoms, heart rate, functional capacity, quality of life and hospitalisations when compared to a sham procedure. Larger, multicentre, double blinded studies are required to generalise the results, though participant blinding cannot be 100% assured. Funding Acknowledgement: Type of funding sources: None.